Optimization of aggregate production costs in textile companies [Optimización de costos de producción agregada en empresas del sector textil] (2020)
This article aims to optimize the aggregate production costs in textile companies sector through production strategies in the medium term. For this, an aggregate production planning model called PLAG is developed, which minimizes labor costs, inventory management costs, and production subcontracting costs. Unlike other models in the literature, the PLAG model considers characteristics of the textile sector related to fabric shrinkage, wastes due to product handling, new employees’ efficiency, training time, and manufacturing processes subcontracting, which makes it a comprehensive and effective model for companies in the textile industry. The proposed model is programmed and executed in GAMS, supported by an interface in MSExcel, which generates strategies for the improvement of the production capacity and the optimization of the production plan. © 2020, Universidad de Tarapaca. All rights reserved.